IoT - AI Mentoring and Diffusion in the Development of Digital-Based Teaching Devices for PAK Teachers - Hartutik, Hartutik; Jay, Dewi Ratna; Pradnya, Matilda Stella; Pradnya, Irene Nindita; Sukestiyarno, YL (Universitas Negeri Semarang, 2025)
Education teacher religion Catholic (PAK) becomes part in system education in Indonesia which follow play a role important in improvement quality education . Improvement self with adapt technology in this 5.0 era become matter important . At this time Still There is difficulty PAK teachers in Semarang City in adapt progress technology especially the Internet of Things (IoT) and Artificial Intelligence (AI). Purpose devotion public This For spread knowledge ( diffusion ) and skills in leveraging IoT and AI in to design device teach education religion Catholic . Activities devotion public This implemented in School St. Francis Catechetical Pastoral College ( STPKat ) Semarang Assisi with amount participants 22 PAK teachers consists of from Elementary, Middle, and High School/Vocational High School teachers in Semarang City. Methods Which applied in devotion is method lecture , with material base law And document church Which support use Internet For kindness His creation , method discussion And ask answer done with method give example And step search application compile device teach PAK with method practice direct search And making in a way independent . Evaluation activity done with give questionnaire pretest -posttest through application Kahoot . Results activity This show existence improvement understanding , knowledge , and skills before And after given diffusion And mentoring utilization of IoT and AI in compile device teach education religion Catholic by 29.31 points .